Cash Waqf in the Halal Blue Economy Sector: A Comparative Study of Indonesia and Malaysia - Ishom, Muhammad; Muttaqin, Entol Zainal; Atikah, Ika; Ghazali, Nasrun Mohamad; Rohmawati, Cucum (Mazahib, 2025)
This study aims to investigate the potential and difficulties of using cash waqf-based sukuk in the growth of the halal industry in the maritime sectors of two nearby nations, Malaysia and Indonesia. Green and blue sukuk have been combined in both nations to aid in the government's endeavors to accomplish the Sustainable Development Goals (SDGs). The main topics of this study's comparative analysis of the policies and strategies in both nations are the implementation mechanisms of cash waqf in supporting blue economy projects and the opportunities and problems encountered. Direct stakeholder observations, interviews, and focus groups in Malaysia and Indonesia provided the research data. Although each nation has a unique method of implementation and regulation, the research findings demonstrate parallels in using cash waqf for sustainable economic growth. Although the integration of green sukuk into blue sukuk has not yet been optimally implemented due to political and theological factors, two Muslim nations with the largest populations and the largest maritime territories have also become pioneers in using cash waqf among Muslim nations worldwide.